Anticipatory Behavior of the Clonal Plant Fragaria vesca - Latzel, Vít; Münzbergová, Zuzana (Frontiers in Plant Science, 2018)
Active foraging for patchy resources is a crucial feature of many clonal plant species. It has been recently shown that plants’ foraging for resources can be facilitated by anticipatory behaviour via association of resource position with other environmental cues. We therefore tested whether clones of Fragaria vesca are able to associate and memorise positions of soil nutrients with particular light intensity, which will consequently enable them anticipating nutrients in new environment. We trained clones of F. vesca for nutrients to occur either in shade or in light. Consequently, we tested their growth response to differing light intensity in the absence of soil nutrients. We also manipulated epigenetic status of a subset of the clones to test the role of DNA methylation in the anticipatory behaviour. Clones of F. vesca were able to associate presence of nutrients with particular light intensity, which enabled them to anticipate nutrient positions in the new environment based on its light intensity. Clones that had been trained for nutrients to occur in shade increased placement of ramets to shade whereas clones trained for nutrients to occur in light increased placement of ramets to light. The ability to predict soil nutrient positions was altered by experimental demethylation. Our study clearly shows that the clonal plant F. vesca is able to relate two environmental factors, light and soil nutrients, and use this connection in anticipatory behaviour. We conclude that anticipatory behaviour can substantially improve the ability of clonal plants to utilize scarce and unevenly distributed resources.